Bevacizumab for ocular neovascular diseases: a systematic review - Andriolo, Regis Bruni (2009)
CONTEXT AND OBJECTIVE: Many eye diseases involve increased local levels of vascular endothelial growth factor (VEGF), and there are several therapeutic strategies for them. Thus, the aim of this study was to evaluate the effectiveness and safety of bevacizumab for treating eye diseases involving increased local levels of VEGF, as the assumed pathophysiological mechanism. DATA SOURCES: The following databases were systematically searched for evidence: PubMed, CENTRAL (Cochrane Library), Literatura Latino-Americana e do Caribe em Ciências da Saúde (Lilacs) and reference lists, without language restrictions. Only randomized controlled trials were included. The primary outcome of interest was visual acuity, irrespective of the evaluation method. DATA SYNTHESIS: A total of 667 eyes in nine randomized trials were included. Meta-analysis showed that the proportion of patients with age-related macular degeneration who presented improvements from baseline regarding best-corrected visual acuity was higher among those treated with bevacizumab than among those in the photodynamic therapy group (risk ratio, RR, 0.49; 95% confidence interval, CI, 0.31 to 0.78; P = 0.01). CONCLUSIONS: The evidence available demonstrates that bevacizumab alone or combined with other treatments is more effective than other options, including photodynamic therapy, focal photocoagulation and triamcinolone. The use of bevacizumab instead of photodynamic therapy could reduce treatment costs by more than 99% and could significantly increase access to treatment. However, long-term studies are still needed in order to reduce uncertainty concerning the safety of this medication for all ocular neovascular diseases in which bevacizumab has the potential to improve visual acuity.